Abnormal uterine bleeding - Whitaker, Lucy (Best Pract Res Clin Obstet Gynaecol, 2016)
Abnormal uterine bleeding (AUB) is a common and debilitating condition with high direct and indirect costs. AUB frequently co-exists with fibroids, but the relationship between the two remains incompletely understood and in many women the identification of fibroids may be incidental to a menstrual bleeding complaint. A structured approach for establishing the cause using the Fédération International de Gynécologie et d'Obstétrique (FIGO) PALM-COEIN (Polyp, Adenomyosis, Leiomyoma, Malignancy (and hyperplasia), Coagulopathy, Ovulatory disorders, Endometrial, Iatrogenic and Not otherwise classified) classification system will facilitate accurate diagnosis and inform treatment options. Office hysteroscopy and increasing sophisticated imaging will assist provision of robust evidence for the underlying cause. Increased availability of medical options has expanded the choice for women and many will no longer need to recourse to potentially complicated surgery. Treatment must remain individualised and encompass the impact of pressure symptoms, desire for retention of fertility and contraceptive needs, as well as address the management of AUB in order to achieve improved quality of life.